2016
DOI: 10.1002/cctc.201600765
|View full text |Cite
|
Sign up to set email alerts
|

Formate to Oxalate: A Crucial Step for the Conversion of Carbon Dioxide into Multi‐carbon Compounds

Abstract: The efficient conversion of formate into oxalate could enable the industrial‐scale synthesis of multi‐carbon compounds from CO2 by C−C bond formation. We found conditions for the highly selective catalytic conversion of molten alkali formates into pure solid oxalate salts. Nearly quantitative conversion was accomplished by calcination of sodium formates with sodium hydride. A catalytic mechanism proceeding through a carbonite intermediate, generated upon H2 evolution, was supported by density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 20 publications
1
59
0
Order By: Relevance
“…Many reaction mechanisms have been proposed, and most recently Lakkaraju et al. suggested carbonite (COO 2− ) as the key intermediate species as shown in Scheme 1 [59] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reaction mechanisms have been proposed, and most recently Lakkaraju et al. suggested carbonite (COO 2− ) as the key intermediate species as shown in Scheme 1 [59] …”
Section: Resultsmentioning
confidence: 99%
“…A recent publication on the topic was from Lakkaraju et al. who introduced hydrides as catalyst and presented a new mechanism [59] . Our work was initially sparked by the many questions still open after reading the previous publications.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of IV from complex II is remarkable, as the direct transformation of formate to oxalate so far has only been achieved via thermal decomposition, calcination or at elevated temperatures and high pressures from bulk CO 3 2− (via formate intermediates) but is unknown in coordination chemistry [40–45] . There are only a few examples for oxalate formation directly from CO 2 [22, 46–52] and one precedent case, where the reaction of formate derived CO 2 2− with CO 2 led to oxalate [19] …”
Section: Resultsmentioning
confidence: 99%
“…(via formate intermediates) but is unknown in coordination chemistry. [40][41][42][43][44][45] There are only af ew examples for oxalate formation directly from CO 2 [22,[46][47][48][49][50][51][52] and one precedent case, where the reaction of formate derived CO 2 2À with CO 2 led to oxalate. [19] Thus,h aving clarified the stoichiometry of the reaction between [L tBu NiOOCH], II,a nd K[N(SiMe 3 ) 2 ], the mechanism of oxalate formation shifted into our focus.Asdiscussed at the end of the last but one section ac onceivable intermediate is,f or instance,[ L tBu Ni I (OCO)C À ]K, A,n amely the product of an intramolecular electron transfer within [L tBu Ni II (CO 2 ) 2À ]K (see Figure 7).…”
Section: àmentioning
confidence: 99%
“…[4][5][6][7][8] Recently, it has been reported that Pd nanoparticles show remarkable activity toward reduction of CO 2 to formate, [9][10][11][12][13][14][15] which can be used as a hydrogen carrier, a fuel in direct formic acid fuel cells and a chemical feedstock for the synthesis of fine chemicals. [16][17][18][19][20][21] Formate production by Pd nanoparticles can proceed close to the thermodynamic potential, and their selectivity for the reduction of CO 2 to formate is quite high. In addition, the large surface area owing to the small particle size allows a high current density, indicating that Pd nanoparticles are a promising CO 2 reduction catalyst.…”
Section: Introductionmentioning
confidence: 99%